2023
DOI: 10.1177/03331024231165682
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, knowledge, perception, and productivity impact of headache education and clinical evaluation program in the workplace at an information technology company of more than 70,000 employees

Abstract: Background Migraine is a highly prevalent, disabling, misunderstood, underdiagnosed, and undertreated neurological disease. It is a leading cause of productivity loss in the workplace. Methods This is the first large-scale company-wide headache education and evaluation program in the workplace. Results 73,432 (90.5%) Fujitsu employees participated. The prevalence of migraine was 16.7%, tension-type headache 40.7%, and cluster headache 0.5%. After completing the training, 82.9% of participants without headache … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The incidence of cluster headaches varies among reports, and the pooled estimates of lifetime prevalence and 1-year prevalence were 124 per 100,000 and 53 per 100,000, respectively [20]. The prevalence of cluster headaches in Japan has been estimated to be around 0.1-0.5% [8,12]. This prevalence rate suggests that the number of patients with cluster headaches is less than one-tenth the number of those with migraine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of cluster headaches varies among reports, and the pooled estimates of lifetime prevalence and 1-year prevalence were 124 per 100,000 and 53 per 100,000, respectively [20]. The prevalence of cluster headaches in Japan has been estimated to be around 0.1-0.5% [8,12]. This prevalence rate suggests that the number of patients with cluster headaches is less than one-tenth the number of those with migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their global impact, there is a notable gap in comprehensive research focused on the clinical characteristics of patients in these settings, particularly in Japan where the prevalence of headaches is comparable to, if not slightly lower than, that observed in Western countries [2][3][4]. Recent efforts by Japanese researchers have highlighted the societal burden of headache disorders [5][6][7][8][9][10][11][12][13][14], yet studies that systematically investigate the clinical pro les of patients attending specialized headache clinics remain remarkably scarce. This gap limits our capacity to tailor patient care effectively and to devise interventions that meet the unique needs of this patient group.…”
Section: Introductionmentioning
confidence: 99%
“…This definition does not account for other patient’s features which are no less important, such as those related to an impaired quality of life due to loss of social life and productivity [ 1 ]. Also, the classic definition does not evaluate the differences related to the geographical distribution of the disease, which is not attributable only to the geographic nuances inherent in each country, but also to the differences in terms of estimation method, the definition that is used for diagnosis but also cultural misconceptions which tend to underestimate migraine as a psychosocial rather than neurobiological disorder [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Japanese researchers have shown growing awareness of the effects of headache disorders on the overall health of the Japanese population [7][8][9][10][11][12][13][14]. These studies have revealed several consequences for people with migraines, including an unmet need for migraine healthcare, increased burden and disability, decreased quality of life, productivity impairment, and employer costs.…”
Section: Introductionmentioning
confidence: 99%